Accident and emergency departments are still failing to assess asthma severity. Issue 4 (1st July 2003) - Harvey, S; Forbes, L; Jarvis, D; Price, J; Burney, P
Abstract : Objectives: To quantify the documentation of vital signs in children attending accident and emergency (A&E) for asthma and to assess whether indicators of severity were used appropriately. Methods: Records of all children aged 3 to 14 attending A&E for the treatment of asthma in four London hospitals over a three month period were examined for documentation of heart rate, respiratory rate, peak expiratory flow rate, oxygen saturation, and fraction of inspired oxygen. The relation between severity indicators and whether the child was admitted or not was examined. Results: There were 255 attendances in 229 children. Heart rate, respiratory rate, and oxygen saturation were recorded on most attendances (94.5%, 85.5%, and 96.8%) but fraction of inspired oxygen and peak flow were recorded in few children (48.6% and 48.5%). Heart rate and respiratory rate were higher and oxygen saturation lower in children who were admitted compared with those who were not. Conclusions: Assessment of airways obstruction is inadequate in children but when measured may be used appropriately to guide admission. There is a need for interventions to improve assessment of children attending A&E for asthma.